An assessment of shape of the longitudinal and the transverse foot arch in male and female pole vaulters - Opanowska, M.; Prietkiewicz-Abacjew, E. (Baltic Journal of Health and Physical Activity, 2015)
Background: The aim of the research was to assess the longitudinal and the transverse shape of the foot arch in male and female pole vaulters. Material/Methods: The research involved 14 women and 16 men training pole vault professionally and possessing the highest level of sport`s proficiency. The assessment of the foot arch was made in static conditions, using a podoscope. The longitudinal foot arch was assessed by Clarke`s method and the transverse foot arch was based on the calcaneal angle. Results: The obtained results showed that the correct and excessive foot arch occur most frequently. Conclusions: Numerous technical exercises performed by pole vaulters on the forefoot and toes strengthen the foot (shortening muscles responsible for a proper level of the longitudinal and the transverse foot arch) and result in the correct or excessive arch in the right and the left foot.